ANALISIS SISTEM ANTRIAN PELAYANAN TIKET KERETA API STASIUN TAWANG SEMARANG - Yustiti, Merlia; Sugito, Sugito; Rusgiyono, Agus (Jurnal Gaussian, 2014)
Semarang Tawang Station is one of the stations visited by customers. As it is known, the train journey is faster than the bus ride. Therefore, it is necessary to analyze queueing models that describe the condition to determine the size of the system performance and to see how the service provided by Customer Service, Ticket Reservation Counters/ Schedule Change/ Refund, Cancellation of the Ticket Counters, and Self Printing Ticket (CTM). Queueing model at the Customer Service and Self Printing Ticket (CTM) is (M/M/2):(GD/∞/∞), Ticket Reservation Counters/ Schedule Change/ Refund is (M/M/4):(GD/∞/∞), and Cancellation of the Ticket Counters is (M/G/1):(GD/∞/∞). Keywords : Arrival Distribution, Queueing Models, Size of the System Performance